The Themes of Universalism and Racial Theology in Acts of the Apostles as a Solution to Discrimination in Nigeria - Offiong Offiong , Asuquo (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
Universalism refers to something that is general and applicable to everybody, while racial theology is the theology which tends to favour one race to the detriment of others. In the book of Acts of the Apostles, Luke who is believed to have written it, highlights this discriminatory racial theology through various events, but at the same time, he tries to debunk and reject this theology by showing that salvation is universal. This paper attempts to relate Luke’s position to the Nigerian society which is characterized by discrimination, tribalism and sectionalism. It advocates that, despite these differences, Nigerians should learn to treat all others like brothers, irrespective of their differences.